Assessing Optimal CO₂ Abatement Policies for the Kyoto Protocol: A Genetic Algorithms Approach - Hiroyuki Kosaka; Takashi Yano (European Regional Science Association (ERSA), 2001)
In 1997, the third Conference of the Parties (COP3) to the United Nations Framework on Climate Change was held. Commitments were set for reducing greenhouse gas emissions in developed countries. Several models have been developed in order to analyze CO2 abatement policies. These models should be categorized as global models considering the wide scale of global warming. Some of those models, however, analyze the policies on a one-country basis and models of global content divide the world into certain regions. It is meaningless to implement the same policies to a region. A multi-country model is preferable to such models. Thus, we have constructed a macroeconometric model linked with an energy model to assess CO2 abatement policies applying genetic algorithms to quantify the optimal policy in favor of the Kyoto Protocol. In this paper, the case of Japan is presented with the intent to analyze optimal policy in a multi-country context.
Keywords: 330